Evaluation of a School-Based Mental Health Program: Grade 8-9 - Berg, Agneta (Kristianstad University, 2015)
The data collection started in 2012 when students in grade 8 answered a questionnaire. The students were followed up after 3 months and after 12 months. Additional data collections are planned when the students are in high school.

The study was performed in grade 8 (students aged 13–15 years, median 14 years) in six municipalities in southern Sweden representing rural and urban areas with a total population of 120 000. There were 23 schools with grade 8 students in the included municipalities, and at 14 schools, a mental health program (the DISA program) was offered in the regular school context. At nine schools, the program was offered to girls only; at two schools, it was offered to girls and boys in separate groups; and at three schools, the program was offered in mixed groups.

The intervention had been delivered at the intervention schools for 2 years on average, with a range of 1–13 years. Three of the control schools had conducted the intervention before but did not do so during the study period. The reasons for this were staff turnover in two schools and priority of the curricular subject in the third school. Schools without this mental health program in their curriculum were recruited as control schools. At 17 of the schools, all students in grade 8 answered the study questionnaires, but at six schools, only girls participating in the mental health program completed the questionnaires due to school administration reasons, and two schools declined to participate. The gender inequity in the intervention and control groups is thus due to that the mental health program is offered to more girls than boys. The questionnaires were completed by 972 students at baseline.

Purpose:

To evaluate a universal school-based mental health program regarding its effectiveness.

Two data collections were conducted in grade 8, with a response rate of 75%. The questionnaires were completed by 972 students at baseline. At the 12-month follow-up, when students were in grade 9, the response rate was 80%.

Studiens datainsamling startade år 2012 då elever i årskurs 8 besvarade ett frågeformulär. Därefter har eleverna följts upp efter 3 månader och efter 12 månader. Ytterligare uppföljningar sker när eleverna går gymnasiet.

Studien genomfördes i årskurs 8 (elever i åldern 13-15 år, median 14 år) i sex kommuner i södra Sverige som representerar både landsbygd och städer med totalt 120 000 invånare. Bland de inkluderade kommunerna fanns 23 skolor med studenter i årskurs åtta, och vid 14 av skolorna fanns ett depressionsförebyggande program (DISA) som erbjöds i den ordinarie skolverksamheten. Vid nio skolor erbjöds programmet endast till flickor, vid två skolor erbjöds programmet till flickor och pojkar i separata grupper, och vid tre skolor erbjöds programmet i blandade grupper. Interventionen vid interventionsskolorna hade i genomsnitt pågått under 2 år, med en räckvidd mellan 1-13 år. Tre av kontrollskolorna hade genomfört interventionen tidigare men inte under studieperioden. Orsakerna till detta var personalomsättningen i två skolor och prioriteten för läroplanens ämne i den tredje skolan. Skolor utan DISA-programmet i kursplanen rekryterades som kontrollskolor.

Vid 17 av skolorna svarade samtliga elever i årskurs 8 på studiens frågeformulär, vid sex skolor besvarades frågeformulären, till följd av administrativa skäl, bara av de flickor som deltagit i programmet. Två av skolorna avböjde att delta. Den ojämna könsfördelningen i interventionsgruppen och kontrollgruppen beror på att DISA-programmet erbjudits till fler flickor än pojkar. Enkäten besvarades av 972 elever vid baslinjemätningen.

Syfte:

Att utvärdera effektiviteten av det skolbaserade programmet DISA.

När eleverna gick årskurs 8 genomfördes 2 datainsamlingar. Vid baslinjemätningen besvarades enkäten av totalt 972 elever. Svarsfrekvensen var 75 % vid de första insamlingarna. Vid 12-månaders uppföljningen, när eleverna gick i årskurs 9, var svarsfrekvensen 80 %.
Att förebygga psykisk ohälsa hos ungdomar med hjälp av systematiska skolbaserade insatser: årskurs 8-9
Keywords: quality of life; livskvalitet; Depression; Depression; youth; ungdom; prevention; prevention; HEALTH; HÄLSA; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin